A study on the influence of physical education teachers’ teaching beliefs and attributions of teaching success and failure on their effective teaching behaviors - Ye Wei (PLoS ONE, 2025)
The study aims to investigate the impact of physical education teachers’ teaching beliefs and attributions of teaching success and failure on their effective teaching behaviors by examining typical quantitative relationships across three dimensions. Five cities in Henan Province were selected using a random sampling method. Within each city, two survey districts were randomly selected, and from each district six to eight primary and secondary schools were randomly chosen, culminating in a total of 64 surveyed primary and secondary schools. A total of 204 physical education teachers from primary and secondary schools were chosen to participate in this study. This research uses questionnaire surveys, semi-structured interviews, t- and F-tests, and canonical correlation analysis to analyse collected data. Results: Teaching experience emerged as a primary factor in influencing teaching beliefs, attributions of teaching success and failure, and effective teaching behaviors (p < 0.05). Teaching beliefs explained 53.2% of the variance in effective teaching behaviors. Attribution of teaching success accounted for 50.9% of this variance in effective teaching behaviors. While attributions of teaching failure explained 49.1% of this variance in effective teaching behaviors. Conclusion: The study recommends setting up a “mentorship system” for physical education teachers to acquire positive teaching experience. This system would enable senior teachers to mentor those with less teaching experience, which in turn motivates senior teachers to be more enthusiastic about teaching. Teachers should have the teaching belief of cultivating students’ success and the ability to communicate with students. Teachers should focus on internal attribution, which is more conducive to teaching success and more effective classroom outcomes. The study concludes that school administrative departments should focus on how teachers attribute their success and failure, and adopt strategies to improve the professional literacy of physical education teachers through promoting teaching reflection, providing regular training, and encouraging collaborative learning among educators.